2013
DOI: 10.5588/pha.12.0071
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and improving data quality from community health workers: a successful intervention in Neno, Malawi

Abstract: Setting A community health worker (CHW) program was established in Neno District, Malawi, in 2007 by Partners In Health in support of Ministry of Health activities. Routinely generated CHW data provide critical information for program monitoring and evaluation. Informal assessments of the CHW reports indicated poor quality, limiting the usefulness of the data. Objectives 1) To establish the quality of aggregated measures contained in CHW reports; 2) to develop interventions to address poor data quality; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…Our results contrast with the other published assessment of HMIS using the WHO report card framework in sub-Saharan Africa, where they found poor data quality ( 24 ). They also differ with most results of different assesments of facility data quality, which also found gaps in data quality pointing to a need for improvement ( 7 15 ) . Another study from Mozambique, using a Global Fund methodology, also found high quality for assessed indicators ( 3 ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our results contrast with the other published assessment of HMIS using the WHO report card framework in sub-Saharan Africa, where they found poor data quality ( 24 ). They also differ with most results of different assesments of facility data quality, which also found gaps in data quality pointing to a need for improvement ( 7 15 ) . Another study from Mozambique, using a Global Fund methodology, also found high quality for assessed indicators ( 3 ).…”
Section: Discussionmentioning
confidence: 62%
“…In most countries, health management information systems (HMISs) serve as the primary data source for national health planning and evaluation ( 2 , 4 ). However, existing evidence suggests variable and often poor quality of this data ( 7 15 ) . In 2009, the World Health Organization (WHO) shared a framework for assessing data quality of HMIS through checks of completeness, internal consistency and external consistency ( 16 ), offering countries a way to measure data quality and identify gaps.…”
mentioning
confidence: 99%
“…In 2015, Neno had 11 health centers and two hospitals offering primary and secondary medical services, respectively. CHWs started working in Neno in 2007 and were primarily assigned to HIV and tuberculosis patients to provide education, accompaniment to medical appointments, psychosocial support, and linkage to formal health services [18]. In 2015, approximately 800 CHWs worked in Neno.…”
Section: Study Setting and Designmentioning
confidence: 99%
“…Leveraging the valuable position of community health workers, many countries have provided training on data collection and use; this both fosters appreciation for data collection tasks and enables active improvement of data quality (e.g. obtaining missing data, following up with patients after referral to determine outcomes, and validating vital registration system data) . A common lesson across interventions is the need to supplement training with supportive supervision, feedback mechanisms, and reliable, timely access to data.…”
Section: Recent Advances and Promising Practicesmentioning
confidence: 99%
“…obtaining missing data, following up with patients after referral to determine outcomes, andvalidatingvital registration systemdata). 41,52,[56][57][58][59][60] Acommonlessonacrossinterventionsistheneed tosupplementtrainingwithsupportivesupervision,feedbackmechanisms,andreliable,timelyaccesstodata.…”
Section: Strategies For Improving Cervical Cancer Data Quality and Usementioning
confidence: 99%